Report of the Malabar Tenancy Committee Volume I the Report - Planning Commission (Planning Commission, 1940)
The Malabar Tenancy Committee Report provides a comprehensive review of land tenure systems in Malabar, focusing on tenant-landlord relations and agricultural productivity. It recommends granting fixity of tenure to all cultivating tenants, establishing fair rent structures based on productivity, and regulating eviction grounds to protect tenant rights. The report emphasizes improving agricultural efficiency through state-managed irrigation, waste land utilization, and standardizing tenancy practices across regions like Gudalur and Kasaragod. It also addresses sub-tenancy issues, financial relief for tenants, and compensation for land improvements. Dissenting opinions advocate for the abolition of landlordism and more radical reforms to ensure that economic benefits directly accrue to cultivators. Overall, the report seeks to balance tenant security with landowner interests, aiming to stabilize agriculture, enhance livelihoods, and create equitable land tenure laws in Malabar.
Madras Printed by the Superintendent Government Press 1940
Madras Printed by the Superintendent Government Press 1940
Keywords: Malabar Tenancy; Tenant Rights; Fixity of Tenure; Fair Rent; Landlordism; Agricultural Productivity; Eviction Policies; Land Reforms; Sub-Tenancy; Gudalur